Enumeration of the Aerobic Bacterial Flora of the House Mouse (Mus musculus) in Akoko South West Local Government Area of Ondo State, Nigeria - Abiose , Festus; Samuel, Sadeko, Samson (African Journal of Education,Science and Technology (AJEST), 2017)
The gastro-intestinal tract of mammals is colonized by a diverse range of microorganisms. House mice (Mus musculus) commonly invade houses where they feed and defecate on foods (raw and processed). This study therefore investigated the gut microbiota of the mice to establish the likelihood of bacterial contamination of these foods by house mice. One hundred and fifty house mice comprising of 76 males and 74 females were trapped with mice-trap from four locations in Akoko South West Local Government area of Ondo State namely Akungba, Ayepe, Iwaro and AAU hostels. The microflora of two different parts (caecum and colon) of the mice’s Gasstro Intestinal Tract were investigated using viable count and cultural methods while the isolates were identified using API kit. Disc diffusion method was used for the susceptibility assessment of the isolates. Mice samples from Ayepe and Adekunle Ajasin University hostels gave the highest microbial count of 27.0 x103 and 25.3x103cfu/mm2 respectively. All the caecum samples gave higher count than their colon counterpart. Eight bacteria species namely Escherichia coli (125), Klebsiella sp (115), Salmonella sp (12), Shigella flexneri (10), Coagulase –ve Staphyloccoci (110), Citrobacter sp (37), Pseudomonas aeruginosa (30) and Lactobacillus sp (65) were isolated with E. coli having the highest frequency of isolation. The isolates (54%) were sensitive to the 4- Quinolones (Ciprofloxacin and Ofloxacin) while 25% were resistant to the Cephalosporins (Cefuroxime and ceftazidime). Poor activities were equally exhibited by Augmentin and Ampicillin. The microorganisms isolated from the GIT of the studied mice were known pathogens. The accesses of the house mice to food or drink items should be prevented through barrier erection and the use of rodent-proof bags for storage of foods and drinks. Prompt treatment is also recommended for infected individuals especially resulting from food contamination/ poisoning.